THEORETICAL AND NUMERICAL ANALYSIS OF FUEL DROPLET COMBUSTION PROCESS WITH CONVENTIONAL AND TRANSIENT MODELS (Journal of Engineering, 2008)
The study introduces a theoretical analysis and numerical solution for the combustion of a hydrocarbon fuel droplet inside the combustion chamber. The study employs two mathematical models to analyze the combustion process. Conventional (Classical) model and Transient model. The combustion process of a stagnant droplet in the steady state was analyzed in the classical model, while, In the transient model, it was assumed that there is a period of time in the stages of the droplet combustion in which the droplet is heated before combustion. The effect of change in temperature on the thermo-physical properties of the fuel was adopted through the two models. For the classical model, a convenient approximation was adopted for the heat transferred inside the droplet.